Foreign Information Manipulation and Interference: the Influence of the Russian Federation on Public Opinion on the Eve of its Full-scale Invasion - Bohdan Yuskiv; Nataliia Karpchuk (Історико-політичні проблеми сучасного світу)
“Foreign information manipulation and interference (FIMI)” is a pattern of behaviour that threatens or has the potential to negatively impact values, procedures and policy processes. Destructive information activity of the Russian Federation in Ukraine and the world showcases such a behaviour. On the eve of the intervention in Ukraine on February 24, 2022, throughout 2021, the RF conducted a powerful special FIMI operation to promote the image of its “extremely strong and invincible army”. We claim that the goal of that FIMI was to intimidate the political elite of Ukraine and ordinary citizens, to eliminate any desire to fight as practically “suicidal”, to induce the state leadership and the President, in particular, to make decisions in favour of the RF. Since Ukrainians give great preference to various Telegram channels as a quick source of “insider” information, the paper scrutinises key messages about the RF army published in 1) the state-owned Russian (RIA Novosti), 2) a number of pro-Ukrainian and 3) Ukrainian pro-Russian Telegram channels. We aim to prove that the publications regarding the image of the Russian army were a RF’s special FIMI operation. Our research shows that the assumption that the RF implemented the special FIMI operation is confirmed. However, the results also indicate that this operation (at least on the part of the state-owned Russian RIA Novosti) was less straightforward and blatant, rather it was more “sophisticated”, although undoubtedly intrusive. This is clearly the manifestation of the “soft power” of this FIMI operation.The paper contributes to further understanding of foreign information manipulation and interference as a growing political problem and a challenge to states’ national security.